Vinyl acetate catalyst and its application
By using a support-supported catalyst of Pd, Au and alkali metal acetate in the ethylene gas phase synthesis method, the absorption peak ratio in the CO-in-situ infrared spectrum is optimized, and the problem of low selectivity of existing catalysts is solved, achieving higher selectivity and synthesis efficiency.
Patent Information
- Application Number
- CN202010958233.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-09-14
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-09-14
AI Technical Summary
In the prior art, the selectivity of ethylene acetate catalyst synthesis by gas phase in ethylene is low, resulting in low synthesis efficiency and product purity.
The catalysts including the support and the Pd, Au and alkali metal acetate supported on the support were optimized by the ratio of the high-wave number and low-wave number absorption peaks in the CO-in-situ infrared spectrum (0.2-0.4).
The selectivity of the catalyst is significantly improved, and the synthesis efficiency and product purity of vinyl acetate are improved.
Smart Images

Figure CN114177938B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst for synthesizing vinyl acetate by an ethylene process and a preparation method thereof, and a method for synthesizing vinyl acetate. Background Art
[0002] As an important organic monomer, vinyl acetate (VAc) is an important raw material for synthesizing chemical products such as polyvinyl alcohol (PVA), polyvinyl acetate (PVA), ethylene-vinyl acetate copolymer resin (EVA), vinyl acetate-vinyl chloride copolymer (EVC) and polypropylene comonomer. It is widely used in synthetic fibers, leather processing, films, vinylon, adhesives, coatings and other fields. Among them, the ethylene gas phase method is one of the most important methods for producing VA in industry at present, which has the advantages of high energy utilization rate and low environmental harm. Especially in recent years, with the opening of the technical route of biomass to ethanol and further dehydration to ethylene, the synthesis of VAc by ethylene gas phase method has received more attention.
[0003] At present, the industrial synthesis of VAc from ethylene by gas phase method mainly uses palladium-gold / potassium acetate / silicon dioxide as catalyst, and the palladium site on the catalyst surface is the main active site. During the reaction, ethylene, oxygen and acetic acid are used as raw materials, and the gas phase catalytic reaction is used to produce vinyl acetate, water and carbon dioxide as a byproduct. The temperature of the reactor shell side of the reaction can be about 100-180°C, the reaction pressure is about 0.5-1.0MPa, and the gas volume space velocity is about 500-3000hr -1 .
[0004] At present, the ethylene vapor phase vinyl acetate catalyst used in industry, such as the patent (CN1226188A) of Herchester Rayon Company, has low selectivity of the catalyst obtained by these methods. Therefore, in view of the above problems, the ethylene vapor phase vinyl acetate catalyst developed by us has better solved the technical problem of low catalyst selectivity. Summary of the invention
[0005] One of the technologies to be solved by the present invention is the technical problem of low selectivity of catalysts prepared by the prior art, and a catalyst for synthesizing vinyl acetate by ethylene process is provided, which has better activity and selectivity.
[0006] The second technical problem to be solved by the present invention is the preparation method of the above catalyst.
[0007] The third technical problem to be solved by the present invention is the application of the above catalyst.
[0008] The fourth technical problem to be solved by the present invention is a method for synthesizing vinyl acetate.
[0009] In order to solve one of the above technical problems, the present invention provides a first technical solution as follows:
[0010] A vinyl acetate catalyst comprising a carrier and Pd, Au and alkali metal acetate loaded on the carrier, wherein the wave number of the catalyst in the CO-in-situ infrared spectrum is 2120-1950cm -1 There is a high wave number absorption peak and a low wave number absorption peak between them, and the wave number corresponding to the peak value of the high wave number absorption peak is 2110~2090cm -1 The peak value of the low wave number absorption peak corresponds to a wave number of 2000-1970 cm -1 The ratio of the peak area of the high wavenumber absorption peak to the peak area of the low wavenumber absorption peak is 0.2 to 0.4.
[0011] When the ratio of the peak area of the high wave number absorption peak to the peak area of the low wave number absorption peak in the CO-in-situ infrared spectrum of the catalyst is in the range of 0.2 to 0.4, the catalyst has a higher selectivity. The ratio of the peak area of the high wave number absorption peak to the peak area of the low wave number absorption peak in the CO-in-situ infrared spectrum of the conventional catalyst is measured to be 0.09 to 0.16, and the selectivity of the catalyst is lower than that of this work.
[0012] In the above technical scheme, the ratio of the peak area of the high wavenumber absorption peak to the peak area of the low wavenumber absorption peak of the CO-in-situ infrared spectrum of the catalyst can be 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40 and the like.
[0013] In the above technical solution, the content of Pd in the catalyst is preferably 1 to 12 g / L. For example, but not limited to, the content of palladium in the catalyst is 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, etc.
[0014] In the above technical solution, the content of Au in the catalyst is preferably 0.1-10 g / L. For example, but not limited to, the content of the promoter metal is 0.2 g / L, 0.3 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L, 1.0 g / L, 1.5 g / L, 2.0 g / L, 2.5 g / L, 3.0 g / L, 3.5 g / L, 4.0 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L, etc.
[0015] In the above technical solution, the content of alkali metal acetate is preferably 10-100 g / L. For example, but not limited to, the content of alkali metal acetate is 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L, etc.
[0016] In the above technical solution, preferably the alkali metal acetate is potassium acetate.
[0017] In the above technical scheme, there is no particular restriction on the shape and size of the carrier, and comparable technical effects can be achieved. For example, but not limited to, the shape of the carrier can be a regular shape such as a sphere, an ellipsoid, a cylinder, a three-leaf plum blossom, or an irregular shape. From the perspective of reducing wear during the operation process, a sphere is preferred. There is no particular restriction on the size of the carrier, for example, but not limited to, when a spherical carrier is used, the diameter of the carrier can be, but not limited to, 3-8 mm.
[0018] In the above technical solution, the carrier is preferably silicon dioxide.
[0019] In the above technical solution, the specific surface area of the carrier is preferably 50 to 250 m 2 / g, for example but not limited to the specific surface area of the carrier is 60m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 110m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g, 170m 2 / g, 180m 2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g and so on.
[0020] In the above technical solution, the pore volume of the carrier is preferably 0.5 to 1.5 cm 3 / g, for example but not limited to the pore volume of the carrier is 0.55cm 3 / g, 0.6cm 3 / g, 0.65cm 3 / g, 0.7cm 3 / g, 0.75cm 3 / g, 0.8cm 3 / g, 0.85cm 3 / g, 0.9cm 3 / g, 0.95cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g and so on.
[0021] In order to solve the second technical problem above, the present invention provides a second technical solution as follows:
[0022] The preparation method of the catalyst for synthesizing vinyl acetate by ethylene process comprises:
[0023] (a) obtaining a solution containing a palladium-containing compound, a gold-containing compound and cyclodextrin as an impregnation solution;
[0024] (b) mixing the catalyst support with the impregnation solution to prepare a catalyst precursor I;
[0025] (c) treating the catalyst precursor I with a solution of an alkaline compound to convert the palladium-containing compound and the gold-containing compound into a precipitated form, thereby preparing a catalyst precursor II;
[0026] (d) reducing the noble metal ions of catalyst precursor II to zero valence to prepare catalyst precursor III;
[0027] (e) Impregnating the catalyst precursor III with alkali metal acetate and drying to obtain a finished catalyst.
[0028] In the above technical solution, the solvent used in the solution of step (a) is preferably water.
[0029] In the above technical solution, the palladium-containing compound is preferably chloropalladic acid.
[0030] In the above technical solution, the gold-containing compound is preferably chloroauric acid.
[0031] In the above technical solution, the cyclodextrin is selected from at least one of the group consisting of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.
[0032] In the above technical solution, the content of cyclodextrin in the impregnation solution is 0.1-1.0 g / L. For example, but not limited to, the content of cyclodextrin is 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L, 1.0 g / L, etc.
[0033] In the above technical solution, the ratio of the volume of the impregnation liquid in step (b) to the volume of the carrier pile is 1.0 to 1.5, for example but not limited to, the ratio of the volume of the impregnation liquid in step (b) to the volume of the carrier pile is 1.1, 1.2, 1.3, 1.4, etc.
[0034] In the above technical solution, the alkaline compound in step (c) is, for example but not limited to, alkali metal silicate.
[0035] In the above technical solution, the solution of the alkaline compound in step (c) is preferably an aqueous solution of the alkaline compound.
[0036] In the above technical solution, the drying temperature in step (e) is preferably 60-90°C, for example but not limited to 65°C, 70°C, 75°C, 80°C, 85°C, etc.
[0037] In the above technical scheme, the drying time in step (e) is preferably 1 to 8 hours, for example but not limited to 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours and the like.
[0038] To solve the third technical problem above, the present invention provides a third technical solution as follows:
[0039] The use of the catalyst described in any one of the technical solutions of the above technical problem or the catalyst obtained by the preparation method according to any one of the technical solutions of the above technical problem in the synthesis of vinyl acetate by ethylene acylation method.
[0040] In order to solve the fourth technical problem above, the present invention provides a fourth technical solution as follows:
[0041] A method for synthesizing vinyl acetate comprises reacting raw gas including oxygen, ethylene, nitrogen and acetic acid in the presence of a catalyst described in any one of the technical solutions of one of the above technical problems or a catalyst obtained by the preparation method of any one of the technical solutions of the second technical problem to obtain vinyl acetate.
[0042] In the above technical scheme, the raw material gas composition is preferably oxygen:ethylene:nitrogen:acetic acid=1:a:b:c in molar ratio, where a=5-7, b=4-8, and c=1-2.
[0043] In the above technical solution, as a non-limiting example, a can be 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9 and so on.
[0044] In the above technical solution, as a non-limiting example, b can be 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.4, 5.6, 5.8, 6.0, 6.2, 6.4, 6.6, 6.8, 7.0, 7.2, 7.4, 7.6, 7.8 and so on.
[0045] In the above technical solution, as a non-limiting example, c can be 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 and so on.
[0046] In the above technical solution, the preferred reaction pressure is 0.5-0.9 MPa, for example but not limited to, the reaction pressure is 0.55 MPa, 0.6 MPa, 0.65 MPa, 0.7 MPa, 0.75 MPa, 0.8 MPa, 0.85 MPa, etc.
[0047] In the above technical scheme, the preferred reaction temperature is 130-200°C, for example but not limited to the reaction temperature of 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C and the like.
[0048] In the above technical solution, the preferred raw gas volume space velocity is 1600 to 3000 hr -1 For example, but not limited to, the raw gas volume space velocity is 1700 hr -1 、1800hr -1 、1900hr -1 、2000hr -1 、2100hr -1 、2200hr -1 、2300hr -1 、2400hr -1 、2500hr -1 、2600hr -1 、2700hr -1 、2800hr -1 、2900hr -1 etc.
[0049] Catalyst Characterization:
[0050] 1. The content of precious metals palladium, gold and potassium is determined by ICP
[0051] The content of potassium acetate is calculated based on the content of potassium.
[0052] 2. CO-in-situ infrared testing
[0053] 2.1. Peel off the precious metal layer on the catalyst surface, grind it into powder, and take 15 mg for tableting;
[0054] 2.2. Use CO2-in-situ infrared to test the products. The test conditions are: evacuate the infrared in-situ pool, then heat it from room temperature to 300℃ within 30 minutes, keep the constant temperature for 120 minutes, and then cool it down to 30℃; then turn off the vacuum and pass CO gas for 10 minutes; then turn off the CO gas and turn on the vacuum to test the sample and collect data.
[0055] 2.3. For CO2 in-situ infrared data processing, the peak position can be obtained by automatic peak search in the OMNIC software; the peak area processing method is as follows: the CO2 in-situ infrared data is imported into the XPSPEAK software, firstly the baseline correction is performed, and then the curve fitting of each peak is performed according to the peak position, and then the peak area is obtained (the software will automatically calculate its peak area). BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is the CO-in-situ infrared spectrum of the catalyst.
[0057] Figure 1 In the figure, curve a is Example 1, curve b is Comparative Example 1, and curve c is Comparative Example 2. DETAILED DESCRIPTION
[0058] Example 1
[0059] 1. Catalyst preparation
[0060] (a) mixing chloropalladic acid, chloroauric acid and α-cyclodextrin with water, stirring at 50° C. for 30 minutes to obtain an aqueous solution as an impregnation solution; the palladium content in the impregnation solution is 2.75 g / L, the gold content is 0.625 g / L, and the α-cyclodextrin content is 0.5 g / L;
[0061] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0062] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0063] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0064] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0065] 2. Catalyst evaluation
[0066] The fixed bed reactor was used for evaluation, and the specific conditions were:
[0067] Catalyst filling volume: 40ml;
[0068] The composition of the reaction raw materials (by molar ratio): oxygen: ethylene: nitrogen: acetic acid = 1: 6.8: 7.2: 1.7;
[0069] Reaction raw material feed volume space velocity: 2000hr -1 ;
[0070] Reaction pressure: 0.7MPa;
[0071] Reaction temperature: 140°C;
[0072] Reaction time: 100hr;
[0073] The content of each component in the reaction product was analyzed by gas chromatography, and then the space-time yield and ethylene selectivity of the catalyst were calculated.
[0074] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0075] Example 2
[0076] 1. Catalyst preparation
[0077] (a) mixing chloropalladic acid, chloroauric acid and α-cyclodextrin with water, stirring at 50° C. for 30 minutes to obtain an aqueous solution as an impregnation solution; the palladium content in the impregnation solution is 2.75 g / L, the gold content is 0.625 g / L, and the α-cyclodextrin content is 0.1 g / L;
[0078] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0079] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0080] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0081] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0082] 2. Catalyst evaluation
[0083] The catalyst evaluation method was the same as in Example 1.
[0084] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0085] Example 3
[0086] 1. Catalyst preparation
[0087] (a) mixing chloropalladic acid, chloroauric acid and α-cyclodextrin with water, stirring at 50° C. for 30 minutes to obtain an aqueous solution as an impregnation solution; the palladium content in the impregnation solution is 2.75 g / L, the gold content is 0.625 g / L, and the α-cyclodextrin content is 0.8 g / L;
[0088] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0089] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0090] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0091] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0092] 2. Catalyst evaluation
[0093] The catalyst evaluation method was the same as in Example 1.
[0094] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0095] Example 4
[0096] 1. Catalyst preparation
[0097] (a) mixing chloropalladic acid, chloroauric acid and α-cyclodextrin with water, stirring at 50° C. for 30 minutes to obtain an aqueous solution as an impregnation solution; the palladium content in the impregnation solution is 2.75 g / L, the gold content is 0.625 g / L, and the α-cyclodextrin content is 1.0 g / L;
[0098] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0099] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0100] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0101] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0102] 2. Catalyst evaluation
[0103] The catalyst evaluation method was the same as in Example 1.
[0104] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0105] Example 5
[0106] 1. Catalyst preparation
[0107] (a) mixing chloropalladic acid, chloroauric acid and β-cyclodextrin with water, stirring at 50° C. for 30 minutes to obtain an aqueous solution as an impregnation solution; the palladium content in the impregnation solution is 2.75 g / L, the gold content is 0.625 g / L, and the β-cyclodextrin content is 0.1 g / L;
[0108] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0109] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0110] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0111] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0112] 2. Catalyst evaluation
[0113] The catalyst evaluation method was the same as in Example 1.
[0114] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0115] Example 6
[0116] 1. Catalyst preparation
[0117] (a) mixing chloropalladic acid, chloroauric acid and β-cyclodextrin with water, stirring at 50° C. for 30 minutes to obtain an aqueous solution as an impregnation solution; the palladium content in the impregnation solution is 2.75 g / L, the gold content is 0.625 g / L, and the β-cyclodextrin content is 0.5 g / L;
[0118] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0119] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0120] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0121] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0122] 2. Catalyst evaluation
[0123] The catalyst evaluation method was the same as in Example 1.
[0124] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0125] Example 7
[0126] 1. Catalyst preparation
[0127] (a) mixing chloropalladic acid, chloroauric acid and β-cyclodextrin with water, stirring at 50° C. for 30 minutes to obtain an aqueous solution as an impregnation solution; the palladium content in the impregnation solution is 2.75 g / L, the gold content is 0.625 g / L, and the β-cyclodextrin content is 1.0 g / L;
[0128] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0129] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0130] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0131] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0132] 2. Catalyst evaluation
[0133] The catalyst evaluation method was the same as in Example 1.
[0134] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0135] Example 8
[0136] 1. Catalyst preparation
[0137] (a) mixing chloropalladic acid, chloroauric acid and γ-cyclodextrin with water, stirring at 50° C. for 30 minutes to obtain an aqueous solution as an impregnation solution; the palladium content of the impregnation solution is 2.75 g / L, the gold content is 0.625 g / L, and the γ-cyclodextrin content is 0.1 g / L;
[0138] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0139] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0140] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0141] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0142] 2. Catalyst evaluation
[0143] The catalyst evaluation method was the same as in Example 1.
[0144] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0145] Example 9
[0146] 1. Catalyst preparation
[0147] (a) mixing chloropalladic acid, chloroauric acid and γ-cyclodextrin with water, stirring at 50° C. for 30 minutes to obtain an aqueous solution as an impregnation solution; the palladium content in the impregnation solution is 2.75 g / L, the gold content is 0.625 g / L, and the γ-cyclodextrin content is 0.5 g / L;
[0148] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0149] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0150] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0151] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0152] 2. Catalyst evaluation
[0153] The catalyst evaluation method was the same as in Example 1.
[0154] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0155] Example 10
[0156] 1. Catalyst preparation
[0157] (a) mixing chloropalladic acid, chloroauric acid and γ-cyclodextrin with water, stirring at 50° C. for 30 minutes to obtain an aqueous solution as an impregnation solution; the palladium content of the impregnation solution is 2.75 g / L, the gold content is 0.625 g / L, and the γ-cyclodextrin content is 1.0 g / L;
[0158] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0159] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0160] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0161] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0162] 2. Catalyst evaluation
[0163] The catalyst evaluation method was the same as in Example 1.
[0164] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0165] Comparative Example 1
[0166] 1. Catalyst preparation
[0167] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, to prepare a catalyst precursor I;
[0168] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0169] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0170] (d) Catalyst precursor III was impregnated with potassium acetate aqueous solution and dried at 80°C for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0171] 2. Catalyst evaluation
[0172] The catalyst evaluation method was the same as in Example 1.
[0173] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0174] Comparative Example 2
[0175] 1. Catalyst preparation
[0176] (a) adding chloropalladic acid and chloroauric acid to an EDTA aqueous solution, stirring at 60° C. for 1 hour, to obtain an impregnation solution; the content of palladium in the impregnation solution is 2.75 g / L, the content of gold is 0.625 g / L, and the content of EDTA is 1.0 g / L;
[0177] (b) Spherical silica carrier (5 mm in diameter, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in the above-mentioned impregnation solution (wherein, the ratio of the volume of the impregnation solution to the volume of the carrier pile was 1.22), and after being immersed for half an hour, the surface of the carrier was dried to obtain a catalyst precursor I;
[0178] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0179] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0180] (e) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0181] 2. Catalyst evaluation
[0182] The catalyst evaluation method was the same as in Example 1.
[0183] For the convenience of comparison, the experimental results are listed in Table 1 and Table 2.
[0184] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
[0185] Table 1
[0186]
[0187] Table 2
[0188]
Claims
1. A method for preparing a catalyst for synthesizing vinyl acetate by ethylene process, characterized in that: The catalyst comprises a carrier and Pd, Au and alkali metal acetate loaded on the carrier. The wave number in the CO-in-situ infrared spectrum of the catalyst is 2120-1950 cm -1 There is a high wave number absorption peak and a low wave number absorption peak between them, and the wave number corresponding to the peak value of the high wave number absorption peak is 2110~2090 cm -1 The peak value of the low wave number absorption peak corresponds to the wave number of 2000~1970 cm -1 , the ratio of the peak area of the high wave number absorption peak to the peak area of the low wave number absorption peak is 0.2~0.4; The preparation method comprises: (a) obtaining an aqueous solution containing a palladium compound, a gold compound and cyclodextrin as an impregnation solution; (b) mixing the catalyst support with the impregnation solution to prepare a catalyst precursor I; (c) treating the catalyst precursor I with a solution of an alkaline compound to convert the palladium-containing compound and the gold-containing compound into a precipitated form, thereby preparing a catalyst precursor II; (d) reducing the noble metal ions of catalyst precursor II to zero valence to prepare catalyst precursor III; (e) Impregnating the catalyst precursor III with alkali metal acetate and drying to obtain a finished catalyst.
2. The preparation method according to claim 1, characterized in that: The cyclodextrin is selected from at least one of the group consisting of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin; and / or, the content of cyclodextrin in the impregnation solution is 0.1-1.0 g / L.
3. The preparation method according to claim 1, characterized in that: In the catalyst, the content of Pd is 1-12 g / L.
4. The preparation method according to claim 1, characterized in that: In the catalyst, the amount of Au is 0.1-10 g / L.
5. The preparation method according to claim 1, characterized in that: In the catalyst, the content of alkali metal acetate is 10-100 g / L.
6. The preparation method according to claim 1, characterized in that: The alkali metal acetate is potassium acetate.
Citation Information
Patent Citations
Palladium-gold catalyst for preparing vinyl acetate
CN1226188A
Vinyl acetate catalyst, preparation method and vinyl acetate synthesis method
CN104437648A
Vinyl acetate catalyst and preparation method thereof
CN104437654A
Method for preparing vinyl acetate catalyst
CN107866277A